2003
DOI: 10.1177/05333164030363015
|View full text |Cite
|
Sign up to set email alerts
|

Practice-Based Evidence for a Brief Time-Intensive Multi-Modal Therapy Guided by Group-Analytic Principles and Method

Abstract: Group analysts are increasingly being called upon to provide effectiveness evidence, which may be critical to the development of group analysis as a therapeutic intervention in National Health Service provision of psychotherapies. This article describes a practice-based outcomes research initiative conducted in a timelimited group-analytic programme. The research was manageable and informative for profiling patients before therapy, recording benefits during therapy, and measuring outcomes at the end of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
(48 reference statements)
1
5
0
1
Order By: Relevance
“…Thus, changes were achieved with regard to both psychological processes and behaviour. Conceptually our findings are suggestive of the possible benefits of developmentally-oriented group psychotherapy for young adults, thus extending the existing body of research on the effectiveness of group interventions (Blackmore et al, 2012; Tschuschke, Anbeh and Kiencke, 2007; Lorentzen, 2006; Conway et al, 2003).…”
Section: Discussionsupporting
confidence: 74%
“…Thus, changes were achieved with regard to both psychological processes and behaviour. Conceptually our findings are suggestive of the possible benefits of developmentally-oriented group psychotherapy for young adults, thus extending the existing body of research on the effectiveness of group interventions (Blackmore et al, 2012; Tschuschke, Anbeh and Kiencke, 2007; Lorentzen, 2006; Conway et al, 2003).…”
Section: Discussionsupporting
confidence: 74%
“…In his introduction to a study published in Group Analysis in 2003, Conway et al described the lack of empirical research in group analytic/dynamic psychotherapy and the barriers to developing such research methods which are present within some areas of the analytic/dynamic psychotherapy community: ‘scepticism and mistrust of researchers and research methodologies, concerns about losing professional identity, lack of scientific education among therapists, and the slow, time-consuming nature of research’ (Conway et al, 2003: 414). Conway et al cautioned the analytic psychotherapy community about the risks of not conducting such research:…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of Clinical Governance into the NHS in 2000 (Department of Health; DH, 1999) has increased the need for psychotherapy services to demonstrate the ‘evidence‐based practice’ for their interventions. Although the ‘evidence‐based practice’ (EBP) paradigm is valuable in establishing the efficacy of an intervention, significant differences between psychotherapy as typically offered during a randomized controlled trial (RCT) and that offered in a routine clinical practice have been identified which place doubts on the generalizability of such interventions (Roth & Parry, 1997; Shadish et al , 1997).…”
mentioning
confidence: 99%